2021
DOI: 10.1097/ccm.0000000000004971
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Thrombosis and Hemorrhage Rates in Patients With Severe Respiratory Failure Due to Coronavirus Disease 2019 and Influenza Requiring Extracorporeal Membrane Oxygenation

Abstract: OBJECTIVES: Extracorporeal membrane oxygenation is a lifesaving therapy for patients with severe acute respiratory distress syndrome refractory to conventional mechanical ventilation. It is frequently complicated by both thrombosis and hemorrhage. A markedly prothrombotic state associated with high rates of venous thromboembolism has been described in patients with severe acute respiratory syndrome coronavirus 2 (coronavirus disease 2019) infection. These rates have currently not been described dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 34 publications
1
59
0
2
Order By: Relevance
“…Characteristics of the selected studies: We identified 5792 citations, of which 113 were retained for full-text evaluation. Twelve articles [12,[17][18][19][20][21][22][23][24][25][26][27], reporting data on 7011 COVID-19 patients and 1,006,484 non-COVID-19 patients, were finally included (Figure 1). The characteristics of the studies are reported in (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the selected studies: We identified 5792 citations, of which 113 were retained for full-text evaluation. Twelve articles [12,[17][18][19][20][21][22][23][24][25][26][27], reporting data on 7011 COVID-19 patients and 1,006,484 non-COVID-19 patients, were finally included (Figure 1). The characteristics of the studies are reported in (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies are reported in (Table 1). Eight studies were retrospective [12,17,18,20,22,[24][25][26], three were prospective [19,21,23], and one was an autoptic evaluation [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We congratulate Doyle et al ( 1 ) on their exciting and clinically relevant report published in a recent issue of Critical Care Medicine comparing thromboembolic complications and bleeding events in coronavirus disease (COVID)–19 acute respiratory distress syndrome (ARDS) with influenza A patients on veno-venous extracorporeal membrane oxygenation (ECMO). The key finding that COVID-19–induced ARDS is associated with higher thromboembolic events despite therapeutic anticoagulation is of high relevance to the community of intensivists.…”
Section: To the Editormentioning
confidence: 99%
“…Anticoagulation strategy in COVID-19 patients on ECMO is further complicated by the co-existence of thrombocytopenia and thromboembolism [ 65 , 66 ]. Therefore, the innate thrombotic potential of ECMO within the emerging evidence of higher thrombotic complications seen in COVID-19 makes it challenging, necessitating a large scale study to establish its clinical utility [ 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%